Awareness on infection prevention measures among ward attendants in a teaching hospital - Dhakal, Prativa; Koirala, Dipti (Journal of Chitwan Medical College, 2025)
Introduction: Infection prevention is an essential measure of patient safety and wellbeing. The medical teams including the cleaning staffs/ward attendants are responsible for preventing infection in both patients and themselves. This study aims to find out the awareness on infection prevention measures among ward attendants working in a teaching hospital, Chitwan.Method: A descriptive cross-sectional study was conducted among 98 ward attendants of Chitwan Medical College Teaching Hospital, Nepal, from 19 Dec 2023 to 02 Jan 2024 using non-probability convenience sampling technique to select the sample. Structured questionnaire interview was used to collect data. Data were analyzed using IBM SPSS version 20 for descriptive and inferential statistics.Result: The study revealed that 56(57.1%) of respondents were ≥26 years of age, 73(74.5%) were female, 55(56.1%) had completed secondary education, 27(27.6%) were working in general wards, and 94(95.9%) had received infection prevention training. The study showed that 83(84.7%) of respondents had high level of awareness regarding infection prevention measures. The level of awareness was found to be significantly associated with the training received by ward attendants on infection prevention measures (p=0.011).Conclusion: The study found that most of the ward attendants had high level of awareness regarding infection prevention measures. There were some specific areas where awareness was lacking, such as the use of sodium hypochlorite solution for disinfection, and the risk of glove tearing using petroleum-based hand lotion which can be addressed through regular training, supervision, and monitoring of infection prevention measures to ward attendants.